2020
DOI: 10.1007/s00213-020-05691-w
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive enhancement effects of stimulants: a randomized controlled trial testing methylphenidate, modafinil, and caffeine

Abstract: Rational At all times humans have made attempts to improve their cognitive abilities by different means, among others, with the use of stimulants. Widely available stimulants such as caffeine, but also prescription substances such as methylphenidate and modafinil, are being used by healthy individuals to enhance cognitive performance. Objectives There is a lack of knowledge on the effects of prescription stimulants when taken by healthy individuals (as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 42 publications
1
28
0
4
Order By: Relevance
“…Specifically, dopamine has been shown to shape large-scale neural networks including prefrontal regions underlying cognitive functions. For this reason, we utilized behavioral and resting state fMRI data from a double-blind randomized placebo-controlled study (see Repantis et al, 2021) and investigated the combined effects of MPH, MOD and CAF on memory and FC at rest (Repantis et al, 2021). We hypothesized that memory performance should increase and large-scale neural networks including prefrontal regions should be modulated as a function of all three stimulants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, dopamine has been shown to shape large-scale neural networks including prefrontal regions underlying cognitive functions. For this reason, we utilized behavioral and resting state fMRI data from a double-blind randomized placebo-controlled study (see Repantis et al, 2021) and investigated the combined effects of MPH, MOD and CAF on memory and FC at rest (Repantis et al, 2021). We hypothesized that memory performance should increase and large-scale neural networks including prefrontal regions should be modulated as a function of all three stimulants.…”
Section: Discussionmentioning
confidence: 99%
“…In the original study two different memory tasks were administered – memory of visual and audio material (see Repantis et al, 2021). For better comparability, we used the same memory outcome measures as reported in Repantis and colleagues (2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the previous four studies, a recent study by Repantis et al suggested improvements in cognitive parameters with caffeine use [16]. In a randomized, double-blind, placebo-controlled study, cognitive performance in 48 male participants (21-36 years old) was assessed after taking one of three stimulants (caffeine, methylphenidate (MHP), modafinil (MOD)).…”
Section: Attention and Processing Speedmentioning
confidence: 99%